Electrical characteristics of the extracellular fluid in the body segments of Apis mellifera bees - Juan Hernandez; Fredy Mesa; Anderson Dussan; Andre Riveros (PeerJ, 2025)
This study investigates the electrical properties of the extracellular fluid in honeybees (Apis mellifera) and its relationship with different body segments. By characterizing resistance, capacitance, and electrical impedance, aspects such as ionic composition, molecular polarization, and the differential response of live bees to electrical stimuli were evaluated. The results show that electrical characteristics vary significantly depending on the body segment, with the head exhibiting high resistance values and the abdomen displaying high capacitance, reflecting differences in molecular composition and functionality. Additionally, experiments with live bees demonstrated the feasibility of measuring electrical parameters non-invasively, opening new possibilities for monitoring the health of these pollinators under controlled conditions and in natural environments. This work lays the foundation for developing innovative tools in ecological monitoring, the assessment of environmental stressors, and the sustainable management of bee colonies.